Formal verification of a space system's user Interface with the IVY workbench - Campos, José C. (2016)
This paper describes the application of the IVY workbench to the formal analysis of a user interface for a safety-critical aerospace system. The operation manual of the system was used as a requirement document, and this made it possible to build a reference model of the user interface, focusing on navigation between displays, the information provided by each display, and how they are interrelated. Usability-related property specification patterns were then used to derive relevant properties for verification. This paper discusses both the modeling strategy and the analytical results found using the IVY workbench. The purpose of the reference model is to provide a standard against which future versions of the interface may be assessed.